EÐ»Ð°ÑÑ‚Ð°Ð·Ð¸ Ð·Ð° ÑƒÐ¼Ð¾Ð² Ð¿Ñ€Ð¸Ñ€Ð¾Ð´Ð½Ð¾Ñ— Ð³Ñ–Ð±ÐµÑ€Ð½Ð°Ñ†Ñ–Ñ— Ñƒ Ñ…Ð¾Ð¼â€˜ÑÐºÑ–Ð² - Samokhina, L. M. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2009)
Natural hibernation in mature male hamsters results in an increased elastase activity and elastase-inhibitory activity (EIA) of Î±-1-inhibitor of proteinases (Î±-1-IP) in the most samples of the studied tissues. An early period of organism recovery (2 hrs after hibernation) is characterised by an increased elastase level and EIA decrease in cerebellum and brain stem, within a later one (24 hrs after hibernation) a balance in the elastase Î±-1-IP system is established.